PHYSICOCHEMICAL AND HEAVY METAL CONTENT ASSESSMENT OF WATER QUALITY IN KEANA AND NASARAWA–EGGON LOCAL GOVERNMENT AREAS, NASARAWA STATE, NIGERIA (FULafia Journal of Science and Technology, 2024)
This study conducted a thorough evaluation of the physicochemical parameters of various drinking water sources in Keana and Nasarawa Eggon, Nasarawa State. The assessment involved the use of standard methods to analyze the water samples. Additionally, the heavy metal contents were determined using the atomic absorption spectrophotometric method. The findings revealed that the pH levels ranged from 7.36 to 8.16 in Keana (KN) and 5.70 to 5.80 in Nasarawa Eggon (NE), with mean pH values of 7.74 and 5.74, respectively. The conductivity varied from 3.94 to 4.56 µS/cm in KN and 510 to 1760 µS/cm in NE. Alkalinity content ranged from 4.06 to 4.52 mgL-1 in KN and 45 to 50 mgL-1 in NE. Nitrate, acidity, chloride, phosphate, TDS, DO, and BOD levels were also assessed. The metal concentrations included Pb, Mn, Cr, Zn, Fe and Cu, and were within permissible limits, except for Pb and Ni, which exceeded WHO specifications. This study provides crucial insights into the water quality of these regions, essential for ensuring the safety of water for human consumption and other activities.
Keywords: Physicochemical; heavy metal; water sources; Keana LGA; Nasarawa–Eggon LGA